PEMANFAATAN ANALISIS POTENSI EKONOMI KREATIF BATIK DALAM INOVASI UNTUK MENINGKATKAN KEUNGGULAN KOMPARATIF PADA MASYARAKAT KABUPATEN KUDUS - Johan Sutarjo (Jurnal Indonesia Sosial Teknologi, 2023)
The Indonesian state is a country that has a lot of potential local wealth as a nation, that potential can be a factor to advance the creative economy in Indonesia including batik, handicrafts, and others. The potential of batik in Indonesia is also found in Kudus Regency which has a very large variety of potentials to be developed, one of which is the creative economic potential of batik. This study has objectives for 1). To find out the creative economic potential of batik in the community of Kudus Regency, 2). To find out how to increase the comparative advantage of the creative economy of batik in the people of Kudus Regency, and 3). To find out the impact of the increase in the creative economy of batik in the community of Kudus Regency. This research uses a qualitative approach. Data collection in that approach can be done by means of observation, documentation, & direct interviews with the owners of Batik Muria & Alfa Shoofa. The results in this study show that: 1) The creative economy of batik in the community of Kudus Regency has great potential that can be developed so that it can compete, with unique & different motifs. 2) How to increase the comparative advantage of the batik creative economy in Kudus Regency, namely with the help of the government that supports the development of the creative economy in Kudus by providing guidance & training. 3) The impact of the potential creative economy of batik in the community of Kudus Regency which includes creating jobs, preserving Kudus culture, plagiarizing many motifs, which is increasingly rampant imitation batik.